Drought Analysis in the Asi Basin (Turkey) - Mehmet Dikici (Doğal Afetler ve Çevre Dergisi)
Climate change is leading one of the main research topic that today’s science world is worried about the future. Increased risks of droughts and floods, resulting from this, have led to the adoption of a holistic understanding of water management in recent years. The tendency of drought should be known in order to manage the increased drought risk and to make a sustainable plan. Drought is a hydrological event that begins and progresses slowly, so monitoring and analysis are of great importance. In addition to many tests, the Mann-Kendall test is one of the most common and respected trend analysis tests. In this study, it was investigated whether there is a drought tendency for the Asi basin, which has an area of ​​about 7800 km2. For this purpose, meteorological, hydrological and hydrogeological data between 1970 and 2016 were considered. The tendency of precipitation, flow, evaporation, temperature and groundwater data for years has been studied in detail and the risk of drought has been investigated for the Asi basin. First of all, meteorology and flow observation stations in the basin were determined to be suitable ones and the missing data were completed by methods appropriate to the literature. As a result of these analyzes, the Asi basin was found to have an upward trend, though not statistically significant, at 95% confidence level in annual total precipitation. On average annual temperatures, there was a clear upward trend for both sub-basins and watersheds.